Financial reporting and global capital markets : a history of the International Accounting Standards Committee, 1973-2000 - Camfferman, Kees, 1966- (Oxford University Press, 2007)
This is a scholarly historical study of the International Accounting Standards Committee (IASC), which prepared the way for the Interational Accounting Standards Board (IASB). The IASB holds the dominant influence over the financial reporting of thousands of listed companies in the EU as well as in many other countries.